2020
DOI: 10.1016/j.energy.2020.116978
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of entropy waves’ evolution for understanding of indirect combustion noise in gas turbine combustors

Abstract: Achieving clean and quiet combustion in gas turbines is essential for improving many low-carbon energy and propulsion technologies. This often requires suppression of combustion instabilities and combustion generated noise in gas turbine combustors. Entropy noise is the less explored mechanism of combustion generated sound. Central to the emission of entropic sound is the survival of entropy wave during convection by the mean flow and reaching the combustor exit nozzle. Yet, the annihilation of entropy waves i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
4
16
0
Order By: Relevance
“…This result was further supported by experimental results in a circular duct (Hosseinalipour et al. 2020). The latter study also showed that the components of the entropy wave with convective wavelengths longer than the duct-diameter remain highly coherent throughout the duct, which supports the use of one-dimensional entropy noise models.…”
Section: Introductionsupporting
confidence: 71%
“…This result was further supported by experimental results in a circular duct (Hosseinalipour et al. 2020). The latter study also showed that the components of the entropy wave with convective wavelengths longer than the duct-diameter remain highly coherent throughout the duct, which supports the use of one-dimensional entropy noise models.…”
Section: Introductionsupporting
confidence: 71%
“…2020; Hosseinalipour et al. 2020), where shear dispersion was identified as the dominant mechanism. There are indeed several mechanisms at play that contribute to the decay of entropy waves (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Eckstein & Sattelmayer 2006;Schulz et al 2019) and with their measurements (Wassmer et al 2017;De Domenico et al 2019). Most of the modelling efforts to date have been about entropy-wave dispersion in fully developed turbulent duct flows (Sattelmayer 2002;Morgans, Goh & Dahan 2013;Morgans & Duran 2016;Giusti et al 2017;Fattahi, Hosseinalipour & Karimi 2017;Christodoulou et al 2020;Hosseinalipour et al 2020), where shear dispersion was identified as the dominant mechanism. There are indeed several mechanisms at play that contribute to the decay of entropy waves (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, however, Bake et al made no attempt to study the spatial evolution of the entropy wave. Most recently, Hosseinalipour et al [28] evaluated experimentally the spatial coherence of the convective entropy waves in a low-speed channel flow. These authors used a network of fast-response thermocouples located at different axial locations along the channel and explored the temporal and spatial decay of the wave [28].…”
mentioning
confidence: 99%
“…Most recently, Hosseinalipour et al [28] evaluated experimentally the spatial coherence of the convective entropy waves in a low-speed channel flow. These authors used a network of fast-response thermocouples located at different axial locations along the channel and explored the temporal and spatial decay of the wave [28]. This study was constrained to simple channels, and thus constant mean flow velocities, and did not consider variable cross-sectional areas.…”
mentioning
confidence: 99%